Econometric evaluation of EU Cohesion Policy: a survey - Tobias Hagen; Philipp Mohl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
More than one third of the European Union's total budget is spent on socalled Cohesion Policy via the structural funds. Its main purpose is to promote the development of the EU and to support convergence between the levels of development of the various European regions. Investigating the impact of European Cohesion Policy on economic growth and convergence is a wide research topic in applied econometric research. Nevertheless, the empirical evidence has provided mixed, if not contradictory, results. Against this background, the aim of this chapter is to provide a fundamental review on this topic. Taking fundamental methodological issues into account, we review the existing econometric evaluation studies, draw several conclusions and provide some remarks for future research.
Keywords: R10; R11; C21; C23; 330; Economic integration; regional growth; EU Cohesion Policy; panel data; spatial econometrics